A novel de novo point mutation of the OCT‐binding site in the IGF2/H19‐imprinting control region in a Beckwith–Wiedemann syndrome patient. (4th December 2013) - Higashimoto, K.; Jozaki, K.; Kosho, T.; Matsubara, K.; Fuke, T.; Yamada, D.; Yatsuki, H.; Maeda, T.; Ohtsuka, Y.; Nishioka, K.; Joh, K.; Koseki, H.; et al.
<x xml:space="preserve">Abstract</x> The IGF2/H19‐imprinting control region (ICR1) functions as an insulator to methylation‐sensitive binding of CTCF protein, and regulates imprinted expression of IGF2 and H19 in a parental origin‐specific manner. ICR1 methylation defects cause abnormal expression of imprinted genes, leading to Beckwith–Wiedemann syndrome (BWS) or Silver–Russell syndrome (SRS). Not only ICR1 microdeletions involving the CTCF‐binding site, but also point mutations and a small deletion of the OCT‐binding site have been shown to trigger methylation defects in BWS. Here, mutational analysis of ICR1 in 11 BWS and 12 SRS patients with ICR1 methylation defects revealed a novel de novo point mutation of the OCT‐binding site on the maternal allele in one BWS patient. In BWS, all reported mutations and the small deletion of the OCT‐binding site, including our case, have occurred within repeat A2. These findings indicate that the OCT‐binding site is important for maintaining an unmethylated status of maternal ICR1 in early embryogenesis.